Monitoring coagulation-fibrinolysis activation prompted timely diagnosis of hemophagocytic lymphohistiocytosis-related disseminated intravascular coagulation - Liqin Ling (BMC, 2021)
Abstract Background Timely diagnosis of disseminated intravascular coagulation (DIC) in hemophagocytic lymphohistiocytosis (HLH) patients is crucial but challenging, as HLH interferes with the results of the laboratory tests included in the DIC score system. Case presentation Here, we reported a case of lymphoma-associated HLH, in which coagulation-fibrinolysis activation /inhibition markers (TAT, tPAIC, and PIC), prompted timely diagnosis of early stage DIC (initial phase of microvascular thrombosis, yet non-overt), prior to the development of organ failures and/or bleedings. Conclusions This report highlights the importance of the implementation of new biomarkers (such as TAT, tPAIC, and PIC), into the diagnostic work-up for coagulation disorders. These biomarkers are directly suggestive of microthrombus formation, therefore they can be of paramount importance in diagnosing DIC with complicated etiologies, such as hematological diseases-related DIC.